Long-Term Health-Related Quality of Life after Breast Reconstruction: Comparing 4 Different Methods of Reconstruction. Issue 6 (June 2017) - Thorarinsson, Andri; Fröjd, Victoria; Kölby, Lars; Ljungdal, Johan; Taft, Charles; Mark, Hans
Abstract : Background: Studies have confirmed that breast reconstruction is beneficial to improve health-related quality of life (HR-QoL) in breast cancer patients. Our aim was to compare 4 different methods of breast reconstruction on patient satisfaction and HR-QoL using both general and specific patient-reported outcome instruments. Methods: Retrospectively, 459 patients who underwent breast reconstruction with a deep inferior epigastric artery perforator (DIEP) flap, latissimus dorsi flap, lateral thoracodorsal flap, or expander with secondary implant and who had responded to the questionnaires were enrolled. Questionnaire answers, together with demographic and follow-up data, were statistically analyzed and compared between groups. Short-Form 36 Health Survey (SF-36) results were also compared with those from a sample of 930 age-matched women from the Swedish population. Results: There were slight differences in the SF-36 results but no significant differences in Psychological General Well-Being Index and EuroQoL-5 Dimension Questionnaire results between groups. Analysis of Breast-Q showed that the DIEP group had significantly higher score on the scale satisfaction with breast, significantly higher score in satisfaction with outcome than the lateral thoracodorsal flap ( P = 0.014) and EXP groups ( P = 0.024). There were no significant differences in most of the domains of the HR-QoL instruments. The higher satisfaction with breasts and outcome in the DIEP group is interesting, considering the higher complication rates associated with this reconstruction method. Conclusions: Patients who underwent breast reconstruction with a DIEP flap were more satisfied with their reconstructed breast and outcome than the other 3 groups. Breast reconstruction centers should make DIEP reconstruction widely available to patients after mastectomy.